ChemInform Abstract: Magnetic Interactions in the Double Perovskites R2NiMnO6 (R: Tb, Ho, Er, Tm) Investigated by Neutron Diffraction. Issue 4 (January 2016) - Retuerto, Maria; Munoz, Angel; Martinez‐Lope, Maria Jesus; Alonso, Jose Antonio; Mompean, Federico J.; Fernandez‐Diaz, Maria Teresa; Sanchez‐Benitez, Javier
Abstract: The title perovskites (obtained from citrate precursors at 900 °C for 12 h) are characterized by XRD, neutron powder diffraction, and magnetic measurements.